Urban Sufism And Transformation Of Islamic Culture In Millenial Society - Shinta Nurani (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper examines Sufism of urban society as a trend of popular Islamic culture in millennial society. Understanding Sufism is a foundation of searching for the alternative life problem solutions, which are currently criticized as being merely temporary and reactionary. Sufism develops from the private sphere into a popular Islamic culture through which to enhance social piety. This popular Islamic culture is a form of repetitive life habits (habitus) that is accepted collectively as a form of general habit. The formation of Sufism habits among urban society initiates the creation of urban Sufism symbols such as piety, hijab, robe, turban, sarong and others. This phenomenon gives birth to how the concepts and practices of Sufism are transformed by members of a tariqa group such as the Tarekat Naqsabandiyah Haqqani Pekalongan. Therefore, the focus of this paper is twofold. The first focus is on the discussion about the way the conventional Sufism transforms into urban Sufism. This transformation denotes a phenomenon of urban Sufism wherein a kiai (English: Javanese terminology referring to a Muslim cleric) acts as an agent of the social transformation in the Naqsabandiyah Haqqani in Pekalongan. The second focus is on the discussion about urban Sufism as a popular symbol of Islam in the millennial era.